Wafer-Scale Vertical 1D GaN Nanorods/2D MoS2/PEDOT:PSS for Piezophototronic Effect-Enhanced Self-Powered Flexible Photodetectors - Tang, Xin; Jiang, Hongsheng; Lin, Zhengliang; Wang, Xuan; Wang, Wenliang; Li, Guoqiang (Nano-Micro Letters, 2024)
van der Waals (vdW) heterostructures constructed by low-dimensional (0D, 1D, and 2D) materials are emerging as one of the most appealing systems in next-generation flexible photodetection. Currently, hand-stacked vdW-type photodetectors are not compatible with large-area-array fabrication and show unimpressive performance in self-powered mode. Herein, vertical 1D GaN nanorods arrays (NRAs)/2D MoS2/PEDOT:PSS in wafer scale have been proposed for self-powered flexible photodetectors arrays firstly. The as-integrated device without external bias under weak UV illumination exhibits a competitive responsivity of 1.47 A W−1 and a high detectivity of 1.2 × 1011 Jones, as well as a fast response speed of 54/71 µs, thanks to the strong light absorption of GaN NRAs and the efficient photogenerated carrier separation in type-II heterojunction. Notably, the strain-tunable photodetection performances of device have been demonstrated. Impressively, the device at − 0.78% strain and zero bias reveals a significantly enhanced photoresponse with a responsivity of 2.47 A W−1, a detectivity of 2.6 × 1011 Jones, and response times of 40/45 µs, which are superior to the state-of-the-art self-powered flexible photodetectors. This work presents a valuable avenue to prepare tunable vdWs heterostructures for self-powered flexible photodetection, which performs well in flexible sensors. Highlights: 1 Vertical 1D GaN nanorod arrays/2D MoS2/PEDOT:PSS heterostructures in wafer scale have been fabricated for flexible photodetection firstly. 2 Self-powered flexible photodetector at compressive strain reveals a significantly enhanced photoresponse with a responsivity of 2.47 A W−1 and response times of 40/45 µs, which are superior to the state-of-the-art flexible devices. 3 This work not only provides a valuable strategy for the design and construction of tunable van der Waals heterostructures, but also opens a new opportunity for flexible sensors.